A Review on Disease Prediction Using Artificial Intelligence - Pallavi Patil; Kirankumari Patil (Journal Electrical and Computer Experiences, 2023)
Artificial Intelligence (AI) can be used for disease prediction in various ways. AI can analyze medical images such as X-rays, MRI scans, CT scans, and mammograms to detect abnormalities and identify potential diseases. This can help in early detection and diagnosis of diseases such as cancer, cardiovascular disease, and neurological disorders. AI can analyze electronic health records (EHRs) to identify patterns and correlations in patient data. This can assist identify patients who are at risk of developing certain diseases and enable proactive intervention.AI can analyze data collected from wearable devices such as fitness trackers and smart watches to monitor health parameters such as heart rate, blood pressure, and sleep patterns. This can help identify early signs of diseases such as hypertension, diabetes, and sleep apnea.AI can analyze patient symptoms and medical history through natural language processing (NLP) to identify potential diseases. This can help healthcare professionals to make a more accurate diagnosis and recommend suitable treatments. Overall, AI has the latent to revolutionize disease prediction by enabling early detection and proactive intervention, which can mend patient outcomes and moderate healthcare costs.